“Des hommes qui s’effeuillent pour des femmes”. Des strip-teaseurs dans un chassé-croisé entre domination masculine et masculinité dominée - Virginie Blum (Recherches Sociologiques et Anthropologiques, 2013)
Striptease has long been framed and considered to be a field of practices traditionally allocated to women, the very first male erotic undressing performances intended for a female audience emerged in the 1970s. In the specific context of men stripping for women, the aim of this paper is to question the modes of reorganization of the gender system men had previously referred to. For instance, does the transgression of gender-oriented practice male stripping involves signal a shift towards an opposite sexual status, or, quite the reverse, lead to a reaffirmation of sexual virility ? On the basis of interviews and empirical observations, we will then analyze the strippers’ masculinity alongside the opposite poles of virility and feminization. On the one hand, we will attempt to demonstrate that the bodily practices engaged in manifest at once visible signs of masculine domination and feminine aesthetics and logics. On the other hand, we will examine the underlying dynamics of the affective relationships between (male) strippers and (female) clients, as evidence of a consumption of heterosexuality, paradoxically both assertive and marginalized among the group of men encountered.